If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3z+7=11
We simplify the equation to the form, which is simple to understand
3z+7=11
We move all terms containing z to the left and all other terms to the right.
+3z=+11-7
We simplify left and right side of the equation.
+3z=+4
We divide both sides of the equation by 3 to get z.
z=1.33333333333
| 6x+1=-6x+1 | | n-31.41=76.50 | | 8x+12x=32 | | 3(2*6)= | | 9x-3=6x+9x+6 | | 3x=77-8x | | -12x-6=10x+4 | | o-325=75 | | k-30=5k-40 | | 9x-2+20x=40 | | Y=1.5x-2 | | (3+w)(4w-7)=0 | | t+3-2t=4t+1 | | -10.2+c=-8014 | | 225*5*5*5*5*5*5= | | 13m+6=-4m | | 1f+5f= | | x+8y=15-8x | | 3(x-1)-2(x-4)=5(x-3) | | 4x-5=10x+12 | | 225*5= | | 2.41=-3.25+k | | 4h-5-6h+11= | | 3x-18=12x | | -9x+15y=-45 | | X^2+10x-105=0 | | 12-4k+5+19k= | | 6+.3(x-7)=.5(2-x) | | 5.28+k=2.38 | | 3x+7y-21=10xy+-21 | | 5h-7=10+5h | | x+14=-2-x |